(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Drug abuse among young people has become a growing concern with serious implications for individuals, families, and society. This study examines the issue from a sociological perspective, focusing on three key areas: the influence of peers, family, and community; the impact of education, unemployment, and media; and the broader consequences for health, family life, education, and employment. Data were collected through an interview schedule consisting of 17 structured questions, administered to 23 students at a government college in Siwani, Bhiwani District, Haryana. The findings reveal that peer pressure plays a significant role in shaping drug-related behaviour, while family support is often moderate and sometimes weak. Respondents expressed mixed views on the protective role of higher education, but most agreed that examination stress and unemployment increase vulnerability. Media was also identified as a strong factor influencing youth attitudes toward drugs. The study further highlights that drug abuse is perceived to have severe effects on health, strain family relationships, harm academic performance, reduce job opportunities, and increase the likelihood of crime or risky behaviour. These insights underline the need for comprehensive interventions involving families, educational institutions, communities, and policymakers to address the complex social dimensions of youth drug abuse.